Spongy elastic silicon-containing negative electrode material and preparation method thereof

By using a variety of carbon sources to construct a three-dimensional mesh structure in the negative electrode material of lithium-ion battery, a sponge-like elastic silicon-containing negative electrode material was prepared, which solved the problems of poor conductivity and volume expansion of silicon materials, and significantly improved the performance of the electrode material.

CN119480959APending Publication Date: 2025-02-18SHANDONG GOLDENCELL ELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507924.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Silicon materials have problems such as large volume expansion, easy particles to pulverize and poor conductivity in the negative electrode of lithium-ion batteries, which makes it difficult to meet practical requirements for electrochemical stability and kinetic performance.

Method used

Through the synergy of multiple carbon sources, a three-dimensional network structure is constructed to prepare a sponge-like elastic silicon-containing negative electrode material to improve conductivity and suppress volume expansion.

Benefits of technology

It effectively improves the conductivity of silicon-based materials, and suppresses volume expansion problems during charging and discharging, improving the overall performance of electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480959A_ABST
    Figure CN119480959A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a spongy elastic silicon-containing negative electrode material and a preparation method thereof. The method comprises the following steps: preparing a precursor by controlling the ratio of a carbon source to a silicon source; performing low-temperature aging on the precursor, and preparing a conductive network of a three-dimensional network structure to obtain a silicon-containing intermediate; and calcining the silicon-containing intermediate at high temperature to obtain the spongy elastic silicon-containing negative electrode material. The invention aims to prepare a three-dimensional spongy carbon layer structure through the synergistic effect of different carbon sources, and improve the volume expansion problem caused by the silicon-containing material in the charging and discharging process, thereby improving the electrochemical performance of the battery. The scheme has the following advantages: through the synergistic effect of multiple carbon sources, the problem of volume expansion of silicon in the charging and discharging process is effectively inhibited; the conductivity of the material can be effectively improved through construction of the spongy three-dimensional net-shaped carbon layer; the spongy three-dimensional structure is beneficial to infiltration of electrolyte, and provides more active sites for intercalation and deintercalation of lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a sponge-like elastic silicon-containing negative electrode material. Background Art

[0002] Silicon has the characteristics of high theoretical specific capacity, low operating voltage and abundant resources, and is considered to be the most promising next-generation lithium-ion battery negative electrode material.

[0003] However, silicon materials also have disadvantages such as large volume expansion (300%), easy pulverization of particles and poor conductivity, which makes it difficult for the electrochemical stability and kinetic performance of the silicon negative electrode to meet practical requirements.

[0004] Carbon materials are widely used as conductive agents in negative electrode materials of lithium batteries. Currently, the performance development of lithium batteries using carbon as a conductive agent has encountered a bottleneck and cannot continue to significantly improve the conductive performance of negative electrode materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a sponge-like elastic silicon-containing negative electrode material. Through the synergistic effect of multiple carbon sources, a three-dimensional network structure is constructed to improve the poor conductivity of silicon-based materials and the volume expansion problem of electrode materials during charging and discharging.

[0006] The present invention is achieved through the following technical solutions: The present invention provides a method for preparing a sponge-like elastic silicon-containing negative electrode material, comprising the following steps: (1) Material preparation: Weigh a certain amount of silicon source, carbon source and dispersant and mix them evenly as a precursor, with the silicon source accounting for 10%-50% of the total mass and the carbon source accounting for 50%-90% of the total mass; (2) Precursor pretreatment: baking the precursor described in (1) at 50-100° C. to generate a three-dimensional network and obtain a silicon-containing intermediate; (3) The silicon-containing intermediate is sintered at high temperature to obtain a sponge-like elastic silicon-containing negative electrode material.

[0007] According to the sponge-like elastic silicon-containing negative electrode material and its preparation method, the silicon source in step (1) is selected from TEOS, nano silicon powder, SiO2, SiO x One or more of .

[0008] According to the sponge-like elastic silicon-containing negative electrode material and the preparation method thereof, the carbon source is selected from two or more of PVP, PVDF, PAN, ascorbic acid, tannic acid, and conductive carbon and mixed.

[0009] According to the sponge-like elastic silicon-containing negative electrode material and the preparation method thereof, the reaction aging time in step (2) is 8-18 hours.

[0010] According to the sponge-like elastic silicon-containing negative electrode material and the preparation method thereof, the reaction solvent in step (2) is one or more of water, ethanol and isopropanol.

[0011] According to the sponge-like elastic silicon-containing negative electrode material and the preparation method thereof, inert atmosphere gas is introduced in step (3), and the inert atmosphere gas is selected from one of nitrogen, argon, and a mixture of nitrogen and argon.

[0012] According to the sponge-like elastic silicon-containing negative electrode material and the preparation method thereof, the sintering process in step (3) is 700-1200° C., the heating rate is 1-10° C. / min, and the sintering time is 3-10 h.

[0013] Compared with the existing technology, the present invention has the following technical effects: (1) By utilizing the synergistic effect of different carbon sources, a three-dimensional sponge-like silicon-containing negative electrode material is prepared, which effectively suppresses the volume expansion problem of silicon-based materials during the charging and discharging process.

[0014] (2) By constructing a three-dimensional network, the conductivity of silicon-based materials can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the sponge-like elastic silicon-containing negative electrode.

[0016] Figure 2 This is the charge and discharge curve of the sponge-like elastic silicon-containing negative electrode. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The method for preparing the sponge-like elastic silicon-containing negative electrode material of the present invention comprises the following steps: (1) Material preparation: Weigh a certain amount of silicon source and carbon source and mix them evenly as a precursor, with the silicon source accounting for 10%-50% of the total mass and the carbon source accounting for 50%-90% of the total mass; the silicon source is selected from TEOS, nano-silicon powder, SiO2, SiO x One or more of the carbon sources are selected from two or more of PVP, PVDF, PAN, ascorbic acid, tannic acid, and conductive carbon.

[0019] (2) Precursor pretreatment: The precursor described in (1) is baked at 50-100° C. for a reaction aging time of 8-18 hours, and a three-dimensional network is generated after baking to obtain a silicon-containing intermediate; (3) The silicon-containing intermediate is subjected to high-temperature sintering, and an inert atmosphere gas is introduced during the sintering, wherein the inert atmosphere gas is selected from one of nitrogen, argon, and a mixture of nitrogen and argon. The sintering process is 700-1200°C, the heating rate is 1-10°C / min, and the sintering time is 3-10h. After sintering, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0020] The present invention is further described with examples: Embodiment 1 comprises the following detailed steps: Step 1), preparation of materials: 5 kg of polyvinyl pyrrolidone PVP and 100 g of tannic acid are dissolved in 25 L of deionized water, stirred and dispersed, and after mixing evenly, 2 kg of nano silicon is added and continued to be stirred and dispersed to obtain a precursor.

[0021] Step 2), the precursor prepared in step 1) of this embodiment is aged at 80° C. for 12 h to obtain a silicon-containing intermediate product.

[0022] Step 3), the silicon-containing intermediate prepared in step 3) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 1000° C. for 10 hours in a sintering furnace. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0023] Embodiment 2 comprises the following detailed steps: Step 1), preparation of materials: 4 kg of polyaniline PAN and 200 g of ascorbic acid are dissolved in a mixed solution of 15 L of deionized water and 5 L of anhydrous ethanol, and the mixture is stirred and dispersed. After uniform mixing, 4 kg of tetraethoxysilane TEOS is added and the mixture is further stirred and dispersed to obtain a precursor.

[0024] Step 2), the precursor prepared in step 1) of this embodiment is aged at 100° C. for 8 h to obtain a silicon-containing intermediate product.

[0025] Step 3), the silicon-containing intermediate prepared in step 2) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 900° C. in a sintering furnace for 12 hours. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0026] Embodiment 3 comprises the following detailed steps: Step 1), preparation of materials: 5 kg of polyaniline PAN and 50 g of conductive carbon are dissolved in 20 L of deionized water solution, stirred and dispersed, and after mixing evenly, 5 kg of SiO is added and continued to be stirred and dispersed to obtain a precursor.

[0027] Step 2), the precursor prepared in step 1) of this embodiment is aged at 70° C. for 8 h to obtain a silicon-containing intermediate product.

[0028] Step 3), the silicon-containing intermediate prepared in step 2) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 800° C. in a sintering furnace for 12 hours. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0029] Embodiment 4 comprises the following detailed steps: Step 1), preparation of materials: 5 kg of polyvinyl pyrrolidone PVP and 100 g of tannic acid are dissolved in 25 L of deionized water, stirred and dispersed, and after mixing evenly, 5 kg of nano silicon is added and continued to be stirred and dispersed to obtain a precursor.

[0030] Step 2), the precursor prepared in step 1) of this embodiment is aged at 80° C. for 12 h to obtain a silicon-containing intermediate product.

[0031] Step 3), the silicon-containing intermediate prepared in step 2) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 1000° C. for 10 hours in a sintering furnace. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0032] Embodiment 5 comprises the following detailed steps: Step 1), preparation of materials: 4 kg of polyacrylonitrile PAN and 200 g of ascorbic acid are dissolved in a mixed solution of 15 L of deionized water and 5 L of anhydrous ethanol, stirred and dispersed, and after mixing evenly, 4 kg of TEOS is added and continued to be stirred and dispersed to obtain a precursor.

[0033] Step 2), the precursor prepared in step 1) of this embodiment is aged at 100° C. for 8 h to obtain a silicon-containing intermediate product.

[0034] Step 3), the silicon-containing intermediate prepared in step 2) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 1000° C. for 10 hours in a sintering furnace. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0035] Embodiment 6 comprises the following detailed steps: Step 1), material preparation: 5 kg of polyacrylonitrile PAN and 50 g of conductive carbon are dissolved in 20 L of deionized water solution, stirred and dispersed, and after mixing evenly, 5 kg of SiO is added and continued to be stirred and dispersed to obtain a precursor.

[0036] Step 2), the precursor prepared in step 1) of this embodiment is aged at 70° C. for 8 h to obtain a silicon-containing intermediate product.

[0037] Step 3), the silicon-containing intermediate prepared in step 2) of this embodiment is placed in a sagger, and nitrogen is used as a protective gas, and the temperature is kept at 1000° C. for 10 hours in a sintering furnace. After the sintering furnace is naturally cooled to room temperature, a sponge-like elastic silicon-containing negative electrode material is obtained.

[0038] The discharge capacity of the samples prepared in the embodiment and the comparative example was measured, and the final material indexes were as follows: Table 1 0.1C discharge capacity (mAh / g) Example 1 1500 Example 2 720 Example 3 890 Example 4 1800 Example 5 680 Example 6 715 According to Table 1, the proportion of Si material in Example 1, Example 2 and Example 3 is 28wt%, 49wt% and 50wt% respectively; the aging temperature and aging time are 80°C, 12h, 100°C, 8h and 70°C, 8h respectively; the sintering temperature in step 3 in Example 1, Example 2 and Example 3 is 1000°C, 900°C and 800°C respectively, and at the same time, the carbon source and silicon source composition in Example 1, Example 2 and Example 3 are also different, but it can be seen from the above table that the discharge capacity of the silicon-containing negative electrode material in Example 1, Example 2 and Example 3 fluctuates within the error range, therefore, the above reaction conditions fluctuate within the experimental minimum value and threshold value and do not affect the preparation of the silicon-containing negative electrode material of the present technical solution; Example 4: Example 4 is different from Example 1 in that the silicon content and the subsequent calcination temperature are different. The discharge capacity of Si@C in Example 4 is 1800mAh / g; Example 5: Example 5 is different from Example 1 in that the carbon source and the silicon source are different. In Example 5, the carbon source is PAN and ascorbic acid, and the silicon source is TEOS. The discharge capacity of the material in Example 5 is 680 mAh / g.

[0039] This technical solution utilizes the synergistic effect between different carbon sources to prepare a multi-layer carbon-coated silicon-containing negative electrode material, effectively suppressing the volume expansion problem of silicon-based materials during charging and discharging, and the unique three-dimensional structure provides more active interfaces for the transmission of lithium ions. It can be seen from Examples 1, 4 and 5 that the carbon source, the silicon source, the ratio between the two and the calcination temperature have a great influence on the performance of the material, and the parameters of Example 5 of this technical solution are the optimal example.

[0040] Example 6: Example 6 is different from Example 1 in that the carbon source and the silicon source are different. In Example 6, the carbon source is PAN and conductive carbon, and the silicon source is SiO. The discharge capacity of the material in Example 6 is 715 mAh / g.

[0041] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a spongy elastic silicon-containing negative electrode material, characterized in that: The following steps are involved: (1) Preparation of materials: Weigh a certain amount of silicon source, carbon source and dispersant, mix them evenly as a precursor, and dissolve them in a reaction solvent; the silicon source accounts for 10%-50% of the total mass of the precursor, and the carbon source accounts for 50%-90% of the total mass of the precursor; (2) Precursor pretreatment: baking the precursor described in (1) at 50-100° C. to generate a three-dimensional network and obtain a silicon-containing intermediate; (3) The silicon-containing intermediate is sintered at high temperature to obtain a sponge-like elastic silicon-containing negative electrode material.

2. A sponge-like elastic silicon-containing negative electrode material and a preparation method thereof according to claim 1, characterized in that: The silicon source in step (1) is selected from tetraethoxysilane TEOS, nano silicon powder, SiO2, SiO x One or more of .

3. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that: The carbon source is selected from two or more of polyvinyl pyrrolidone (PVP), polyvinylidene fluoride (PVDF), polyaniline (PAN), ascorbic acid, tannic acid and conductive carbon, and the mixture is mixed.

4. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that The reaction aging time in step (2) is 8-18h.

5. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that: The reaction solvent in step (2) is one or more of water, ethanol and isopropanol.

6. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that: In step (3), an inert atmosphere gas is introduced, and the inert atmosphere gas is selected from one of nitrogen, argon, and a mixture of nitrogen and argon.

7. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that: In step (3), the sintering process is 700-1200°C, the heating rate is 1-10°C / min, and the sintering time is 3-10h.

8. The sponge-like elastic silicon-containing negative electrode material and the preparation method thereof according to claim 1, characterized in that: In step (1), the dispersant is polyvinyl pyrrolidone (PVP) or polyaniline (PAN).